PENGEMBANGAN PRODUK MINUMAN SARI BUAH TOMAT DAN BEKATUL SEBAGAI MINUMAN FUNGSIONAL - Lilik Kustiyah; Evy Damayanthi; Henry Farizal (Faculty of Agricultural Technology, University of Jember, 2014)
Tomato and rice bran are highly potential as source of antioxidant.But, proper processing need to optimize its potency as source of antioxidant.The objective of this experimental research was to develop tomato juice (TJ) and rice bran (RB) drinkwhich high content of its active compound. Preparation of material was making TJ and RB powder. To make TJ was used 2 treatment, i.e. blanching and filtering To improve acceptance of RB drink, it was addition of flavor (vary in type and concentration) to RB powder, and then applied organoleptic test to get the best acceptance of RB drink. Then,analyzing of nutrient content (NC) and soluble fiber (SF) of TJ and RB powder, and total carotene (TC) of TJ were applied. Development of this functional drink and its content analyzes was done at Laboratory of Community Nutrition Department, Bogor Agricultural University. Result showed that NC, SF and TC of TJ between treatment weren’t significantly different (p>0.05). TC of TJ was blanched-unfiltered (TJBU), blanched-filtered (TJBF), not blanched-unfiltered (TJNU), and not blanched-filtered (TJNF) were 13.7641, 12.4835, 13.7132, dan 12.2867 ppm, respectively. SF of TJBU, TJBF, TJNU, TJNF, and RB powder were 4.49%, 3.09%, 4.92%, 4.76%, dan 6.53%, respectively. The best acceptance of RB drink was flavored by 0.75%. cappuccino. So, TJ and RB drink can be used as an alternative of functional drink.Keywords: carotene, flavor, functional drink, rice bran, tomato